Concentration and composition of PM10 in outdoor and indoor air in industrial area of Balakong Selangor , Malaysia - Norela Sulaiman,; Maimon Abdullah,; Phyllis Lo Poh Chieu, (Universiti Kebangsaan Malaysia, 2005)
Air quality study was carried out to determine the concentration and composition of PM10 in the indoor and outdoor air quality of the mixed residential and industrial areas of Balakong in Selangor. Measurements of PM10 concentrations were carried out for 48 hours at eight sampling stations by using the Mini Volume Sampler, with the flow rate of 0.005L per minute. The composition of PM10 such as anions (sulphates, nitrates and chlorides), cations (potassium, calcium, sodium, magnesium, ammonium) as well as the heavy metals (lead, zinc, iron, nickel, cadmium) were determined by standard methods. The concentration of anions was determined by using Spectrophotometer from HACH while the concentrations of cations and heavy metals were determined by Inductively Coupled Plasma-Optical Emission Spectrophotometry (ICPOES). The PM10 concentration of indoor air was found to be higher than those of the outdoors in the study area (p<0.05). Concentrations of outdoor air PM10 were found to be influenced by wind speed (R2 = 0.5324) and humidity (R2 = 0.5299), while the indoor air of different buildings were found to be influenced by frequency of cooking activities (R2 = 0.5698). The PM10 composition of the air for both the indoors and outdoors showed the same order of the concentrations of anions, viz; NO3- > SO42- > C1- . Likewise, for cations and heavy metals the orders of relative concentration were: Na+> Ca2+> K+> Mg2+ and Zn> Fe> Mn>Cr, respectively.